Scientific Impact of Central and Eastern European Higher Education Lecturers - Sajter, Domagoj (Naše gospodarstvo/Our economy, 2021)
The purpose of this paper is to obtain and analyse data on the higher education lecturers at the 16 largest, state-owned faculties of economics in seven central and eastern European countries (Bosnia and Herzegovina, Croatia, Kosovo, Montenegro, North Macedonia, Serbia, and Slovenia), about their scientific impact and reach. An analysis of their research areas and scientometrics (citations, h-indices) was performed, and aggregate rankings are presented. Data was collected from Google Scholar, Web of Science and Scopus by using proprietary specialized web crawlers (“bots”). The differences among countries and faculties are significant, and institutions should observe good practices from Slovenia, as its faculties are ranked highest. The insights are important for evaluating scientific progress, mobility, and cooperation, rewarding and promotion requirements, accreditations, project and institution funding, and higher education lecturers’ promotion.